Pengadaan Rumah Gembira Sebagai Langkah Untuk Menekan Ketergantungan Anak Pada Smartphone - Maulana, Izzul Haq Firman; Pratama, Gilang Tangguh; Nalendra, Dava; Mubarok, Muhammad Furqon; Hamid, Wildan Bagas; Basyari, Lc., M.Ud, Dr. Fathurrohman Muhammad (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Rumah Gembira is a learning and playing facility for children in the digital era. The problem that occurs in the community of Ciater Village is the rampant use of smartphones among young children. Children in Ciater Village always play online games until they forget other mandatory activities. Therefore, we, the students of KKN SISDAMAS UIN SGD Bandung Group 405, organised Rumah Gembira and Tutoring with the aim of reducing the use of smartphones in children. The target of Rumah Gembira is elementary school students in Ciater Village, Ciater District, Subang Regency. The implementation of this work programme begins with playing together and introducing traditional games and contemporary games such as stunting snakes and ladders. In addition, we also provide education about hygiene and moral education. The results of this work programme activity are children who are getting to know traditional games again and less children playing smartphones, so that children’s enthusiasm for learning increases.